PSIKOLOGI SOSIAL DALAM PENELITIAN AKUNTANSI MANAJEMEN - Yunus, Muh. Kafrawi (Jurnal Ilmiah Ecosystem, 2016)
Social Psychology been very meaningful in its application for aperformance management accounting for progress and greatness of a companythrough the theories that relate to the motivation and information supported withits preliminary theory/derivatives is very meentukan for the passage of a healthcare company. These writings reveal theory of levels of Aspiration,PenetapanTujuan Theory, a theory of cognitive dissonance Theory,Organizational Considerations, the theory of Attribution Theory, Expectancy, andthe theory of Person-environment Fit, all of which support the anticipation ofthose effects in companies that can degrade the performance of the company.This article concludes that the practice of management accounting judgmentand decisions affect not only by providing information, but also by influencinghow boundedly rational individuals search and process this information andmentally represent their organization and environment.